Analysis of influencing factors for subcutaneous effusion after cranioplasty - LIU Yang; ZHANG Wen⁃yi; WANG Yun⁃peng; ZHAO Kun; WANG Jian; LIU Ai⁃xian (Chinese Journal of Contemporary Neurology and Neurosurgery)
Objective To explore the influencing factors for subcutaneous effusion (SCE) after cranioplasty. Methods Total of 111 patients with skull defect who underwent cranioplasty from January 2019 to June 2024 in Beijing Rehabilitation Hospital, Capital Medical University were analyzed retrospectively. All the patients were devided into SCE group (n = 29) and non⁃SCE group (n = 82) according to whether they had SCE after cranioplasty. Univariate and multivariate Logistic regression analyses were applied to explore the influencing factors for SCE after cranioplasty. Results Among 111 patients, 29 had SCE after cranioplasty, with an incidence of 26.13%. All the 29 patients recovered and there was no bleeding, scalp damage, implant exposure, poor wound healing and intracranial infection after the treatment. Logistic regression analysis showed that age increase (OR = 1.075, 95%CI: 1.027-1.126; P = 0.002), polyether ⁃ ether ⁃ ketone (PEEK) repair material (OR = 7.673, 95%CI: 2.227-26.435; P = 0.001) and 24 h drainage increase before drain removal (OR = 1.026, 95%CI: 1.008-1.044; P = 0.004) were risk factors for SCE after cranioplasty. Conclusions Age increase, PEEK repair material and 24 h drainage increase before drain removal were risk factors for SCE after cranioplasty. Timely and effective interventions should be taken according to individual condition.